2008
DOI: 10.1111/j.1600-051x.2008.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of supportive periodontal care for patients with chronic periodontitis

Abstract: SPC delivered in specialist as compared with general practice will result in greater stability of clinical attachment but this will be achieved at relatively greater cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 71 publications
(179 reference statements)
4
87
0
6
Order By: Relevance
“…It is also more cost efficient to provide maintenance in primary care. 49 Primary Care Trusts (or whatever body replaces their function) should recognise that periodontal disease demands flexible management. It is known that the UDA system does not accommodate the complexities and temporal demands of many dental treatments.…”
Section: Resultsmentioning
confidence: 99%
“…It is also more cost efficient to provide maintenance in primary care. 49 Primary Care Trusts (or whatever body replaces their function) should recognise that periodontal disease demands flexible management. It is known that the UDA system does not accommodate the complexities and temporal demands of many dental treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently any comparative analysis requires assumptions over the additional effectiveness of alternative/more intensive treatment. Previous comparative analysis (Gaunt et al 2008) estimated attachment loss and tooth loss over thirty years using published data (clinical reference data) (Axelsson and Lindhe 1981). Axelsson and Lindhe (1981) report attachment loss and tooth loss for patients receiving either 40 or 120 minutes of clinician's time annually.…”
Section: Effectiveness Of Spcmentioning
confidence: 99%
“…In a previous, UK-based, study of cost-effectiveness we concluded that SPC delivered in specialist periodontal practice would result in greater periodontal stability and higher tooth survival rates than when SPC is delivered in general dental services. These benefits, however, were more expensive with Incremental Cost-Effectiveness Ratios (ICERs) of approximately €290 for each extra tooth-year saved and €1500 per 1mm less attachment loss over a 30-year period (Gaunt et al 2008). The costs averted from preserving the dentition did not entirely offset the costs of SPC provided by periodontal specialists after appropriate discounting (Gaunt et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pershaw et al [27], ont montré que les résultats cliniques entre pratique générale et spécialisée au Royaume-Uni restent comparables à court terme pourvu que l'omnipraticien suive les instructions du praticien spécialiste avec un contrôle de plaque rigoureux. Toutefois, une méta-analyse plus récente [28] évaluant l'efficacité de la maintenance entre les deux types de pratique a conclu que la thérapeutique de maintenance parodontale chez un spécialiste a montré une meilleure stabilité des résultats du traitement parodontal et un meilleur taux de survie des dents.…”
Section: Adhésion Au Traitementunclassified